2022
DOI: 10.3390/nu14235049
|View full text |Cite
|
Sign up to set email alerts
|

Adzuki Bean MY59 Extract Reduces Insulin Resistance and Hepatic Steatosis in High-Fat-Fed Mice via the Downregulation of Lipocalin-2

Abstract: Adzuki bean is well known as a potential functional food that improves metabolic complications from obesity and diabetes. Lipocalin-2 (LCN2) has been implicated to have an important role in obesity and diabetes. However, the protective roles of adzuki bean MY59 extract (ABE) on insulin resistance and hepatic steatosis are not fully understood. In the present study, we investigated the effects of ABE on LCN2 expression in high-fat diet (HFD)-fed mice. ABE reduced HFD-induced fat mass and improved insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Hyperglycemia is one of the T2D-related outcomes for studying the effectiveness of diabetes management. High-fat diets have been found to contribute to higher blood glucose levels, and various studies have used high-fat diets as one of the means to induce high blood glucose in mice [ 10 , 36 , 37 , 38 , 39 ]. All these investigations found that supplementing high-fat diets with adzuki bean flour could improve such conditions.…”
Section: The Role Of Adzuki Bean Supplements In Managing T2d Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperglycemia is one of the T2D-related outcomes for studying the effectiveness of diabetes management. High-fat diets have been found to contribute to higher blood glucose levels, and various studies have used high-fat diets as one of the means to induce high blood glucose in mice [ 10 , 36 , 37 , 38 , 39 ]. All these investigations found that supplementing high-fat diets with adzuki bean flour could improve such conditions.…”
Section: The Role Of Adzuki Bean Supplements In Managing T2d Outcomesmentioning
confidence: 99%
“…Mice that received an adzuki bean extract in their diet were found to have better glucose regulation and pancreatic function [ 10 , 38 , 39 ]. An animal study providing 3-week-old male C57BL/6 mice with a high-fat diet consisting of 45% kcal from fat found that the high-fat diet significantly increased fasting blood glucose level, serum insulin, insulin resistance, and the Langerhans islet area of β-cells ( p < 0.05) [ 38 ]. Adding 200 mg/kg BW/day of adzuki bean extract to the high-fat diet of the mice significantly reduced the increased parameters ( p < 0.05).…”
Section: The Role Of Adzuki Bean Supplements In Managing T2d Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A few animal studies have investigated the anti-diabetic effects of organic solvent extracts from oats [ 21 ], sorghum [ [22] , [23] , [24] ], adzuki bean [ 25 , 26 ], and black soybean [ 27 , 28 ]. However, there is limited research comprehensively evaluating the effects of extracts on not only hyperglycemia but also insulin sensitivity and pancreas damage.…”
Section: Introductionmentioning
confidence: 99%